Multiple Cross and Inbred Strain Haplotype Mapping of Complex-Trait Candidate Genes - Park, Yeong-Gwon; Clifford, Robert; Buetow, Kenneth H.; Hunter, Kent W. (Genome Research, 2003)
Identifying complex-trait candidate genes after initial low-resolution mapping has proven to be a difficult and labor-intensive undertaking, usually requiring years to develop and analyze congenic strains. As a result, to date, few complex-trait genes have been discovered. Recently it was suggested that SNP haplotype analysis in inbred strains might be useful for mapping of complex traits. In this study, we have combined medium-resolution haplotype mapping with multiple experimental cross-mapping experiments to reduce the number of potential candidate genes in a complex-trait candidate interval. Coincident mapping of a modifier gene in multiple experimental crosses using different inbred strains is consistent with the common inheritance of a modifier allele. A haplotype map was developed in four inbred strains of mice used in our complex-trait mapping crosses across the proximal 10 cM of proximal Chromosome 19 to identify haplotype blocks that segregate appropriately. Only ∼23 out of >400 genes met this criteria. This strategy coupled with tissue and expression arrays, as well as our recently described common pathway analysis to reduce the number of high-priority candidates, may provide a rapid, efficient method to identify and prioritize complex-trait candidate genes without requiring construction of congenic mouse strains.
10.1101/gr.786403